Jurnal Spektrum Hukum Konflik Norma Pasal 15 Ayat (2) Dan Ayat (3) Undang-Undang Nomor 42 Tahun 1999 Tentang Jaminan Fidusia (Studi Putusan MK Nomor 18/PUU-XVII/2019) - Firman Ikhsan (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
The rights of Fiduciary guarantees, in practice, are often violated by Fiduciary guarantee recipients. Even thuggery methods are used for this purpose. The purpose of this study was to identify and analyze the legal norms formulated in Article 15 of the Fiduciary Guarantee Law and the conflicting norms of Article 15 paragraph (2) and paragraph (3) of the Fiduciary Guarantee Law with the original intense formulation of Article 28G paragraph (1) of the 1945 Constitution of the Republic of Indonesia . The research method uses a normative juridical approach. Legal norms which are the legal substance of the formulation of the Fiduciary Guarantee provisions are analyzed through a concept and law approach. Fiduciary towards the 1945 Constitution, caused by the phrase "executive power" and the phrase "the same as a court decision that has permanent legal force" which is contrary to the principles of legal certainty and fairness of the parties to the agreement. The legal argument is the subjectivity of creditors (Fiduciary Recipients) in assessing and determine the circumstances of default (default) of the debtor (Fiduciary Provider).